P07.01 CD19 CAR T-cells for relapsed/refractory diffuse large B-cell Lymphoma: real-world data from LMU Munich. (1st October 2020) - Bücklein, V; Blumenberg, V; Schmidt, C; Rejeski, K; Ruzicka, M; Müller, N; Reischer, A; von Baumgarten, L; Völkl, A; Wagner, B; Humpe, A; Tischer, J; et al.
Abstract : Background: The anti-CD19 CAR T-cell products Axicabtagene Ciloleucel (Axi-cel) and Tisagenlecleucel have been approved by the EMA for the treatment of patients (pts) with relapse/refractory (r/r) diffuse large B-cell lymphoma (DLBCL) in August 2018. In clinical trials, both cell products induced ongoing complete responses in heavily pretreated patients. However, this activity was associated with significant toxicity. We evaluated the outcomes of DLBCL pts treated with Axi-cel and Tisagenlecleucel at the LMU Munich. Materials and Methods: CAR T cell product characteristics, toxicity and response rates of pts treated at our center between January and October 2019 were retrospectively assessed. Results: As of October 2019, 24 out of 34 r/r DLBCL pts (71%) with confirmed CAR T cell treatment indication were leukapheresed. Four apheresed pts died before CAR T cell therapy due to rapidly progressive disease. So far, 17 DLBCL pts have been treated. Median age was 60 years (range 19–74). ECOG was 0–1 in eleven, and 2–3 in six pts. Eight pts had undergone prior stem cell transplant (6 autologous, 2 allogeneic SCT). 13 pts received bridging chemotherapy between leukapheresis and CAR T cell transfusion. Only 6 (35%) of the 17 transfused pts would have met the inclusion criteria of the pivotal clinical trials (JULIET, ZUMA-1). CRS occurred in all pts (53% CRS °1, 29% °2 and 18% °3) with a median onset on day 2 (range days 0–7) and a median duration of 4 days (range 1–21). Tocilizumab was administered at least once in all pts. Ten pts (59%) experienced Immune Effector Cell associated Neurotoxicity Syndrome (ICANS, 30% °1, 10% °2, 30% °3, 20% °4 and 10% °5) with a median onset between day 7 and 8 and a median duration of 8 days (range 3–49). Cytopenia was significant following CAR T-cell treatment: all but one pts had neutropenia <500/µl for more than seven days. Response assessment four weeks after CAR T-cell transfusion was available for 15 pts. Objective response rate (ORR) at this early follow-up was 67%, with complete remission (CR) in four (27%) and partial remission (PR) in six pts (40%). Interestingly, ORR was higher in the four pts not receiving bridging chemotherapy between leukapheresis and CAR T-cell therapy than in pts in which bridging was applied (100% vs. 55%). Responders had significantly higher LDH levels at apheresis, start of lymphodepletion and CAR T-cell transfusion than non-responders. Conclusions: Since January 2019, the CAR T cell program has been successfully initiated at the LMU Munich, and 17 r/r DLBCL pts have been treated at our center to date. CAR T cells induced responses in heavily pretreated pts with response rates within the expected range. Toxicity was significant but manageable in most pts. Involvement of a multidisciplinary ImmunoTaskforce was a key element for adequate patient care. Preliminary data supports the hypothesis that low tumor dynamics are associated with favorable outcomes of CD19 CAR T cell therapy. Disclosure Information: V. Bücklein: None. V. Blumenberg: None. C. Schmidt: None. K. Rejeski: None. M. Ruzicka: None. N. Müller: None. A. Reischer: None. L. von Baumgarten: None. A. Völkl: None. B. Wagner: None. A. Humpe: None. J. Tischer: None. H. Stemmler: None. M. von Bergwelt: None. M. Subklewe: None.